Selected information on microfinance in Bangladesh. - Credit and Development Forum (Bangladesh) (Dhaka : Credit and Development Forum, 2001)
Chiefly statistical tables.
Description based on: Vol. 11 (June 2000).
Microfinance data bank of MFI-NGOs.
Keywords: Microfinance -- Bangladesh -- Periodicals; Microfinance -- Bangladesh -- Statistics